Performance Evaluation of Petbox: A Low Cost Bench Top Preclinical Pet Scanner - Rannou-Fuentes, F (2011)
Purpose: PETbox is a low cost bench top preclinical PET scanner dedicated to pharmacokinetic and pharmacodynamic mouse studies. A prototype system was developed at our institute, and this manuscript characterizes the performance of the prototype system. Procedures: The PETbox detector consists of a 20×44 bismuth germanate crystal array with a thickness of 5 mm and cross-section size of 2.05×2.05 mm. Two such detectors are placed facing each other at a spacing of 5 cm, forming a dual-head geometry optimized for imaging mice. The detectors are kept stationary during the scan, making PETbox a limited angle tomography system. 3D images are reconstructed using a maximum likelihood and expectation maximization (ML-EM) method. The performance of the prototype system was characterized based on a modified set of the NEMA NU 4-2008 standards. Results: In-plane image spatial resolution was measured to be an average of 1.53 mm full width at half maximum for coronal images and 2.65 mm for the anterior-posterior direction. The volumetric reconstructed resolution was below 8 mm3 at most locations in the field of view (FOV). The sensitivity, scatter fraction, and noise equivalent count rate (NECR) were measured for different energy windows. With an energy window of 150 - 650 keV and a timing window of 20 ns optimized for mouse imaging, the peak absolute sensitivity was 3.99% at the center of FOV and a peak NECR of 20 kcps was achieved for a total activity of 3.2 MBq (86.8 ?Ci). Phantom and in vivo imaging studies were performed and demonstrated the utility of the system at low activity levels. The quantitation capabilities of the system were also characterized showing that despite the limited angle tomography, reasonably good quantification accuracy was achieved over a large dynamic range of activity levels. Conclusions: The presented results demonstrate the potential of this new tomograph for small animal imaging. © Academy of Molecular Imaging and Society for Molecular Imaging, 2010.